Meta-Analysis of the Effects of Sleep Duration, Exercise, and Family Income on Obesity in Children - Hanifah Hanifah; Arddha Maha Pawitra Dwi Puspita Dewi; Arinda Mukti Yuhanani; Jemmi Sastrawijayah; Bhisma Murti; Siti Mar’atul Munawaroh (Journal of Epidemiology and Public Health, 2023)
Background: Obesity is still one of the problems in Indonesia. The obesity problem has grown into an epidemic, with more than 4 million people dying each year. Factors causing obesity such as lifestyle, lack of physical activity, poor diet habits, low family income, sleep duration, and others. This study aims to estimate the effect of sleep duration, exercise, and family income on obesity in children. Subjects and Method: A systematic review and meta-analysis were conducted using PRISMA guidelines and the PICO model. Population= children of 2-18 years. Intervention= short sleep duration, exercise, and high family income. Comparison= long sleep duration, no exercise, and low family income. Outcome= Obesity. Articles were collected from databases such as Google Scholar, PubMed, Science Direct, and ResearchGate. The literature search used the keywords “family income" AND “exercise” AND "sleep duration" AND “obesity” AND “children” AND "cross-sectional". A total of 19 articles met the inclusion criteria for the meta-analysis, and subsequently were assessed using RevMan 5.4. Results: A meta-analysis of studies from Japan, Korea, Ethiopia, China, Morocco, Saudi Arabia, and Ghana showed that children with short sleep duration (aOR= 1.83; CI 95%= 1.22 to 2.73; p= o.003), children with high family income (aOR= 1.18; CI 95%= 1.03 to 1.36; p= 0.020) could increase the incidence of obesity, and those results were statistically significant. Exercise can reduce the incidence of obesity in children, but this risk of reduction was not statistically significant (aOR= 0.80; CI 95%= 0.59 to 1.09; p= 0.15o). Conclusion: Short sleep duration and high family income increase the incidence of obesity in children, and these results are statistically significant. Exercise decreases the incidence of obesity in children, but the risk of decline is not statistically significant. Keywords: family income, exercise, sleep duration, obesity, children Correspondence: Hanifah. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: hanifah1611@gmail.com. Mobile: +6281226829788.